Screening and identification strategy for 317 pesticides in fruits and vegetables by liquid chromatography-quadrupole time-of-flight high resolution mass spectrometry1. Issue 15 (7th August 2015) - Wang, Zhibin; Chang, Qiaoying; Kang, Jian; Cao, Yanzhong; Ge, Na; Fan, Chunlin; Pang, Guo-Fang
<x xml:space="preserve">Abstract</x> A screening and identification method was set up for routine qualitative detection of multi-pesticide residues in fruits and vegetables based on a home-made accurate database and spectral library.